Ketimpangan Persebaran Penduduk di Cilegon Banten dan Dampaknya terhadap Pembangunan Wilayah - Muhammad Haris Al Ayyubi; Muhammad Miftah Farid; Akrom (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the inequality of population distribution among sub-districts in Cilegon City and its impact on regional development in terms of infrastructure, public services, and community welfare. Based on data from the Central Statistics Agency of Cilegon City from 2024 to 2025, it was found that population distribution is highly uneven, with a population density in Cilegon District reaching 5,300 people per square kilometer, more than five times higher than that of Ciwandan District. This inequality is caused by five main factors: the centralized pull of the industrial area, infrastructure disparities, low absorption of local labor, economic oligarchy practices, and the lack of affordable housing in the southern region. The resulting impacts include infrastructure overcapacity of up to 135 percent, inequality in access to public services, and a paradoxical condition between a high Human Development Index of 79.54 and a sharp increase in the Open Unemployment Rate to 7.41 percent. This study recommends the decentralization of economic centers to the southern region, the development of north-south connectivity, improvement of local labor competencies, and inclusive governance.